Quality in Design and Execution of Engineering Practice - L.A. van Gunsteren (Research in Design Series, 2013)
Quality in Design and Execution of Engineering Practice is about quality management focused at fitness for purpose, rather than compliance with specifications, rules and regulations. The focus on getting execution in line with fitness for purpose is supported by a classification of seven different categories of quality, defined by their relevance for purpose, compliance with specifications, and actual execution. This classification facilitates decision making on desirable exemptions from specifications in the interest of both buyer and supplier. The author offers guidelines for quality management in different types of business units: License Giver, License Taker, Jobber and Consultant. Real life examples illustrate the author's approach, which concerns a mindset rather than a recipe for effective quality management. The book is of interest to any manager who is striving for superior quality of products and services for his customers.